The Influence of Interpersonal Intelligence and Learning Independence on the Chemistry Learning Outcomes of Grade X Students at SMAN 15 Pekanbaru - Melani, Wiren Arta; Herdini , Herdini; Wulandari, Putri Adita (Chemistry Education Practice, 2025)
This study aims to determine the influence of interpersonal intelligence and learning independence on students' chemistry learning outcomes in grade X of SMA/MA or equivalent. This research employed a quantitative approach using a survey method. The sample consisted of 152 grade X students from SMA Negeri 15 Pekanbaru. The instruments used were questionnaires and documentation of students’ chemistry learning scores. Data analysis techniques included descriptive statistics, correlation tests, and multiple linear regression, assisted by SPSS version 25. The results showed that interpersonal intelligence had a significant effect on learning outcomes with a significance value of 0.042 (<0.05), contributing 34%. Learning independence also had a significant effect on learning outcomes with a significance value of 0.025 (<0.05), contributing 58%. Simultaneously, interpersonal intelligence and learning independence had a positive and significant influence on students’ chemistry learning outcomes, with a combined contribution of 58.1%. The conclusion of this study is that interpersonal intelligence and learning independence are two crucial factors that support students' success in chemistry learning.